The Double Drum Peel (DDP) test: A new concept to evaluate the delamination fracture toughness of cylindrical laminates. (October 2018) - Daghia, F.; Cluzel, C.; Hébrard, L.; Churlaud, F.; Courtemanche, B.
Abstract: Standard delamination tests of monolithic composites prescribe configurations where the crack is a symmetry plane for both overall geometry and stacking sequence, ensuring a controlled mode ratio. These normalized configurations do not enable testing of curved specimens, like those manufactured by filament winding. Here, we propose a new concept for the delamination testing of cylindrical laminates, the Double Drum Peel, related to the peel tests used for adhesives or thin-films debonding. A global energy analysis, including all sources of energy release and dissipation, provides the expression of the critical strain energy release rate. As in the classical peel test, the energy dissipated by mechanisms other than delamination should be accounted for to determine intrinsic interface properties. The local mode mixity is evaluated based on analytical results on the classical peel test. Tests using carbon-peek rings manufactured by laser assisted tape placement are presented to illustrate the potential of the DDP.